Detective Department - Språkbanken Text (University of Gothenburg, 2024)
The Detective Department project is based on texts from the Gothenburg police, from the late 1800s to the early 1900s. These texts have been transcribed manually. Work is in progress at Språkbanken to further develop this data. So far, the texts are not available here, but they can be found at Riksarkivet. One part of our project consists of finding on a map the places mentioned in the texts. This address data is available here, in two files. One file contains geographical coordinates, the other coordinates in the map file we have used.

Projektet Detektiva avdelningen baseras på texter från Göteborgspolisen, från slutet av 1800-talet till början av 1900-talet. Texterna har transkriberats manuellt. Arbete pågår på Språkbanken med att vidareutveckla datan. Än så länge finns inte texterna här, men går att hitta hos Riksarkivet. En del av vårt projekt är att markera på en karta de platser som omnämns i texterna. Den adressdatan finns tillgänglig här, i två filer. Den ena filen innehåller geografiska koordinater, den andra koordinater i den kart-fil vi har använt.
Detektiva avdelningen
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik